Carbon Nanomaterials Embedded in Conductive Polymers: A State of the Art - Gómez, I Jénnifer; Vázquez Sulleiro, Manuel; Mantione, Daniele; Alegret, Nuria (Polymers, 2021)
Carbon nanomaterials are at the forefront of the newest technologies of the third millennium, and together with conductive polymers, represent a vast area of indispensable knowledge for developing the devices of tomorrow. This review focusses on the most recent advances in the field of conductive nanotechnology, which combines the properties of carbon nanomaterials with conjugated polymers. Hybrid materials resulting from the embedding of carbon nanotubes, carbon dots and graphene derivatives are taken into consideration and fully explored, with discussion of the most recent literature. An introduction into the three most widely used conductive polymers and a final section about the most recent biological results obtained using carbon nanotube hybrids will complete this overview of these innovative and beyond belief materials.
Keywords: polyaniline; carbon dots; carbon nanotubes; conjugated polymers; poly(3,4-ethylenedioxythiophene), polypyrrole; graphene